Carboxyl and thiol-functionalized magnetic nanoadsorbents for efficient and simultaneous removal of Pb(II), Cd(II), and Ni(II) heavy metal ions from aqueous solutions: Studies of adsorption, kinetics, and isotherms. (January 2023) - Kothavale, V.P.; Sharma, A.; Dhavale, R.P.; Chavan, V.D.; Shingte, S.R.; Selyshchev, O.; Dongale, T.D.; Park, H.H.; Zahn, D.R.T.; Salvan, G.; Patil, P.B.
Abstract: Magnetic nanoparticles (MNPs) are important adsorbents for removing heavy metal ions (HMIs) from water due to their high surface area, abundant active adsorption sites after functionalization, magnetic separability, and reusability. However, compared with removing a single type of metal ion (single system), the simultaneous removal of multiple coexisting types of HMIs (e.g., ternary system) is challenging. To address this issue, in this study, Fe3 O4 MNPs were functionalized with thiol (–SH) and carboxylic (–COOH) groups using meso-2, 3-dimercaptosuccinic acid (DMSA). The MNP-DMSA nanoadsorbent was used for the simultaneous removal of Pb(II), Ni(II), and Cd(II) from aqueous solutions. The nanoadsorbent was extensively characterized and its adsorption behavior was investigated based on kinetic and isotherm studies using batch adsorption experiments. Highly monodispersed MNPs with the size of 8.24 ± 1 nm and the pure magnetite phase were synthesized using the thermal decomposition method. Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy analyses confirmed the successful modification of the surfaces of the MNPs by DMSA ligands. The MNP-DMSA nanoadsorbents exhibited good colloidal stability according to zeta potential measurements. The maximum adsorption capacities (qm ) for the simultaneous removal of Pb(II), Ni(II), and Cd(II) in the ternary system were determined as 64.5, 53.9, and 27.18 mg/g, respectively. In single systems, the qm values for Pb(II), Ni(II), and Cd(II) were increased to 116.54, 102.73, and 75.48 mg/g, respectively. The adsorption kinetics and isotherm followed Langmuir and pseudo-second order models, respectively. An adsorption/desorption experiment demonstrated the reusability of the nanoadsorbent. Graphical abstract: Image 1 Highlights: Highly monodispersed MNPs of 8.24 nm size with pure magnetite phase. Functionalization of MNPs with DMSA (MNP-DMSA) using a ligand-exchange protocol to simultaneously remove heavy metal ions. Maximum adsorption capacities for Pb(II), Ni(II), and Cd(II) are 64.5, 53.9, and 27.18 mg/g in a ternary metal ion system, respectively. Adsorption kinetics and isotherm study follow Langmuir and pseudo-second-order models, respectively. Good regeneration performance of MNP-DMSA nanoadsorbents.